Penerapan Terapi Dzikir terhadap Penurunan Tingkat Ansietas Pasien Pre Operasi - Robi Aidi; Aprida Manurung; Bangun Dwi Hardika (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Anxiety is an emotional condition characterized by excessive worry about various daily life events whose objects are unclear. Anxiety can arise in various situations, one of which is when facing pre-operation where a person feels anxious during the anesthesia and surgical process. Applying evidence-based practice of dhikr therapy, it was concluded that dhikr therapy was useful for reducing preoperative anxiety levels. The level of anxiety before being given dhikr therapy in respondents 1,2,3 and 5 was at moderate anxiety level and respondent 4 was at severe anxiety level. After dhikr therapy was given, it was found that the anxiety level in respondents 1,2,3 and 5 decreased to mild anxiety and respondent 4 decreased to moderate anxiety.